The 2014 effusive eruption at Stromboli volcano (Italy): Inferences from soil CO2 flux and 3He/4He ratio in thermal waters. Issue 7 (14th April 2015) - Rizzo, Andrea Luca; Federico, Cinzia; Inguaggiato, Salvatore; Sollami, Aldo; Tantillo, Mariano; Vita, Fabio; Bellomo, Sergio; Longo, Manfredi; Grassa, Fausto; Liuzzo, Marco
Abstract A new eruption started at Stromboli on 6 August 2014, which had been preceded by 2 months of increased Strombolian activity and several lava overflows from the craters. The eruption was characterized by a lava effusion in Sciara del Fuoco from a fracture at 650 m above sea level that lasted until 13–17 November. Here we present the first geochemical observations of this eruption, based on the soil CO2 flux in the summit area and on 3He/4He ratios in the thermal waters near Stromboli village. We infer that this eruption was triggered by the gradual replenishment of the feeding system by a CO2‐ and 3He‐rich magma at the end of 2013 and after June 2014, suggested by the increase in 3He/4He ratio before eruption, which reached its highest value since 2007. We thus infer that this eruption was unusual, and we finally speculate on the evolutionary scenario of posteruption.